Choose the right backup for your business. - Waring, Becky
Companies often fail to appreciate a sound data backup strategy until their data goes missing. Fortunately, good, affordable backup technology is plentiful, with a flavor for every taste.
Keywords: Hard disks (Computer science); Electronic data processing -- Backup processing alternatives; Data recovery (Computer science); Direct-attached hard drives; Network-attached storage; Portable storage; USB portable hard disks; Online storage